A QUESTÃO DE LIVROS DA ESCOLA-MODELO BENEDITO LEITE: cultura material escolar e poder disciplinar no Maranhão (1900-1911) - Licar, Ana Caroline Neres Castro (2010)
This work to analyze the historical nature of power relations - from the perspective Foucaultians - within the public school's primary capital of Maranhão, in the first decade of the twentieth century. In this analysis, the object of study has been controversy over the books of the Model School Benedito Leite, especially The Writings Rudimentary Primer (1908), involving Barbosa Godoy, author of the booklet and director of the Normal and Model Schools, and Antonio Lobo, Inspector Public Instruction in 1911. The rejection of the primer, to initiate the reading of the 1st year of School Model, by Inspector of Public Instruction, gave rise to intense debate regarding the application of intuitive and analytical methods. As background to the controversy, highlights the struggle for power understood as true discourse in the educational field, fought between Lobo and Godoi through his speeches materialized in the newspaper Diario do Maranhão. This work is entered in the field of material culture school and the methodology used was based on circumstantial paradigm of Ginzburg (1989), where, through the analysis of the sources, we sought evidence of the use of technologies employed in power relations within the school field. For this analysis were used, regulations, laws, decrees, newspaper articles and works published by those involved in the controversy. It was found that the school is a place of power relations, where the disciplinary power through hierarchical supervision, control the activity and time were the main power devices used in view of the civilizing project of the nation.